How occupational health is assessed in mine workers in Murmansk Oblast - Skandfer, Morten; Siurin, Sergei; Talykova, Ljudmila; Øvrum, Arild; Brenn, Tormod; Vaktskjold, Arild (International Journal of Circumpolar Health, 2012)
Objectives : We aimed to describe how work exposure and occupational health is assessed for mine workers in Murmansk Oblast, Russia. Study design : A descriptive study based on current practice, laws and available literature. Methods : The information and data were obtained from scientific publications, reports, regional and federal statistics, legal documents, through personal visits and on-site inspections. Results : Several institutions are involved in these assessments, but all mine workers have been examined by specialists at one institution, which helps to ensure that the work is of stable quality and adds reliability value to the numbers. Workplace risks are assigned hazard grades, which influence the frequency of periodic medical examinations and salary levels. The examinations are aimed to diagnose latent or manifest occupational disease. This may lead to relocation to a workplace with lower exposure levels, free medical treatment, compensation and a lower pension age. Conclusions : Regulations and systems to protect the health of mine workers have more emphasis on control and repair than on prevention. Since relocation can lower the salary, some workers may under-report medical problems. To what degree this happens is unknown. The mining enterprises pay the medical service provider for periodic medical examinations, which could potentially weaken their independent role. This framework is important to understand when studying and assessing the health of working populations in the circumpolar region.